2020
DOI: 10.1111/1462-2920.15032
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen flux into metabolites and microcystins changes in response to different nitrogen sources inMicrocystis aeruginosaNIES‐843

Abstract: The over-enrichment of nitrogen (N) in the environment has contributed to severe and recurring harmful cyanobacterial blooms, especially by the non-N 2fixing Microcystis spp. N chemical speciation influences cyanobacterial growth, persistence and the production of the hepatotoxin microcystin, but the physiological mechanisms to explain these observations remain unresolved. Stable-labelled isotopes and metabolomics were employed to address the influence of nitrate, ammonium, and urea on cellular physiology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…Furthermore, an adaptive management approach is needed to determine if the 40% reduction goal needs to be adjusted with changes in land use practices and climate change [99]. Additionally, future studies should focus on drawing direct functional links between nutrient enrichment and cyanotoxin production, e.g., Krausfeldt et al [36]. Lastly, anatoxin should be more closely monitored in WLE, as it is a potent neurotoxin with human health-associated implications [100].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, an adaptive management approach is needed to determine if the 40% reduction goal needs to be adjusted with changes in land use practices and climate change [99]. Additionally, future studies should focus on drawing direct functional links between nutrient enrichment and cyanotoxin production, e.g., Krausfeldt et al [36]. Lastly, anatoxin should be more closely monitored in WLE, as it is a potent neurotoxin with human health-associated implications [100].…”
Section: Discussionmentioning
confidence: 99%
“…There is an urgent need to determine the linkage between different bioreactive forms of N and P and the promotion of toxic CyanoHABs, to establish the necessary reduction in these nutrient forms to ensure the security of surface potable water. Nutrient reduction will likely need to be even greater as climate change increases the N and P reduction thresholds required for CyanoHAB mitigation [35,36]. The in situ bioassay-based study reported here is among the first to use an experimental approach to investigate the response of a natural CyanoHAB community dominated by either Microcystis (Maumee Bay) or Planktothrix (Sandusky Bay) to actual reductions in N, P or both, under natural conditions in Lake Erie.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are differences in gene expression associated with utilizing the nitrogen sources and changes in activity of enzymes involved in nitrogen assimilation when cyanobacteria are exposed to each of the nitrogen sources, NO 3 − , NH 4 + , and urea [14][15][16]. The physiological response of cyanobacteria to nitrogen sources also varies according to the species [13,17]. We previously reported that when Synechocystis sp.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, we performed a combination of in vivo 15 N-labeling of metabolites and metabolome analysis. The 15 N-labeling technique is applied to detect metabolites of interest in cyanobacteria or to examine the metabolic behavior of a few metabolites [2,17,21,22]. This technique enables us to compare the metabolic turnover under different nitrogen sources by calculating the 15 N labeling rate at each time point.…”
Section: Introductionmentioning
confidence: 99%